solve by cramer's rule
Attachments:
![](https://hi-static.z-dn.net/files/dea/350e412759b74a677adcd3f35417ba2e.jpg)
Answers
Answered by
4
x + y = -1 -----------------------(1)
y + z = 1 ------------------------(2)
x + z = 0 ------------------------(3)
From Eqn. (3) x = -z
now putting x = -z in (1)
y - z = -1 ---------------------------(4)
adding (2) and (4)
y = 0
Hence, z = 1 and x = -1
Answered by
0
Holaaa Mate
Refer to the attachment...
Attachments:
![](https://hi-static.z-dn.net/files/d45/b594a87a5656c591c2d5407fe99d0f83.jpg)
Similar questions